Enhancing Chemistry Literacy through Project-Based Worksheets on Pineapple Peel-Based Body Lotion Production in Senior High School Students - Ghefira Az-Zikra; Risa Rahmawati Sunarya; Sari; Riri Aisyah; Iis Dahriah; Dadan Ahkyar Alhammadani (Jurnal Pendidikan Kimia FKIP Universitas Halu Oleo, 2026)
This study aimed to examine the effectiveness of project-based worksheets utilizing pineapple peel waste in improving senior high school students’ chemistry literacy in body lotion production. A pre-experimental one-group pretest–posttest design was employed involving 17 Grade XI students at MA Al Jawami, Bandung. The learning process was implemented through Project-Based Learning (PjBL) stages, including problem identification, project planning, investigation, product development, evaluation, and dissemination. Data were collected using a chemistry literacy test covering content, context, process, and attitude dimensions as well as a scientific attitude questionnaire. Data were analyzed using descriptive statistics, normalized gain (N-gain), and the Wilcoxon Signed-Rank Test. The results showed an improvement in students’ chemistry literacy after the implementation of the project-based worksheets with a high category. These findings indicate that project-based worksheets are effective in enhancing students’ chemistry literacy through contextual and experiential learning.